Species sorting and stoichiometric plasticity control community C:P ratio of first‐order aquatic consumers. (11th May 2017) - Teurlincx, Sven; Velthuis, Mandy; Seroka, Dominika; Govaert, Lynn; van Donk, Ellen; Van de Waal, Dedmer B.; Declerck, Steven A. J.
Abstract: Ecological stoichiometry has proven to be invaluable for understanding consumer response to changes in resource quality. Although interactions between trophic levels occur at the community level, most studies focus on single consumer species. In contrast to individual species, communities may deal with trophic mismatch not only through elemental plasticity but also through changes in species composition. Here, we show that a community of first‐order consumers (e.g. zooplankton) is able to adjust its stoichiometry (C:P) in response to experimentally induced changes in resource quality, but only to a limited extent. Furthermore, using the Price equation framework we show the importance of both elemental plasticity and species sorting. These results illustrate the need for a community perspective in ecological stoichiometry, requiring consideration of species‐specific elemental composition, intraspecific elemental plasticity and species turnover.